Formulation of Cultural Values Internalization Policy by Regional Government: Efforts to Mitigate the Negative Impact of Globalization on Children - Patawari, Patawari; Wikra Wardhana Mamonto, Moch Andry (Dinasti Research, 2023)
The inevitability of the rapid flow of globalization has had particularly negative implications among children, and previous research has even revealed that it has resulted in the erosion of cultural values and even the extinction of several languages. This focus examines the efforts that should be made by Regional/Regency Governments to curb the negative impacts of globalization. To answer the focus of the problem, legal-normative research methods are used, using a conceptual approach and a statutory regulatory approach. This research examines primary legal materials and secondary legal materials, then analyzed qualitatively. Based on the authority of the Regional/Municipal Government, the government's efforts to mitigate negative impacts can be carried out by internalizing cultural values among children through drafting regional regulations regarding local content curricula containing confirmation of preparation, development, implementation and supervision.